Shifting Gears: Competition Strategies of Legacy Automakers Like Volkswagen with Electric Vehicle Innovators Like Tesla for Market Dominance in the Global Electric Vehicle Sector - Karimov, Arastun (My University, 2026)
This thesis analyzes the competitive strategies utilized by traditional automakers, namely Volkswagen, and the reaction to the disruptive emergence of electric vehicle (EV) innovators such as Tesla. This is the dynamic power change in the worldwide electric vehicle market by examining critical variables, including technological advancement, regulator adaptability, consumer perception, a strategic innovation. A mixed-method approach, including semi-structured interviews, and quantitative survey research was employed to evaluate the impact of institutional characteristics assumer expectations and R&D investments on business performance. The data indicates that Tesla’s initial advantage stemmed from vertical integration software development agility and brand positioning while traditional manufacturers also with the closing the gap substantial investments, restructuring and strategic partnerships. Nonetheless enduring organizational inertia and deficiencies in customer trust continue to impede incumbents. The report offers strategic ideas to assist both traditional and creative companies in managing the continuous shift towards sustainable mobility.
Keywords: Electric vehicles -- Economic aspects.; Electric vehicles industry -- Technological innovations.; Competition -- Automobile industry.; Strategic planning -- Automobile industry.; Sustainable transportation.